Pseudoangiomatous Stromal Hyperplasia: A Case Report. (9th January 2011) - Masannat, Yazan A.; Whitehead, Stephen; Hawley, Ian; Apthorp, Lesley; Shah, Elizabeth F.
Abstract : Pseudoangiomatous stromal hyperplasia (PASH) is a rare benign proliferating breast condition. It was first reported in 1986 when Vuitch, Rosen, and Erlandson described nine cases of benign well-circumscribed, breast masses that simulated vascular lesions consisting of mammary stromal proliferations (Vuitch et al. (1986)). Since then there have been few reported cases of PASH in the literature (Taira et al. (2005)). We describe a large PASH, mimicking inflammatory carcinoma in a young lady that was excised with excellent cosmetic results.